PENGEMBANGAN VIDEO ANIMASI PROSES TERJADINYA TSUNAMI SEBAGAI SALAH SATU UPAYA PENGURANGAN RISIKO BENCANA - Latifah, Novitia; Wahyono, Unggul; Werdhiana, I Komang (Universitas Tadulako, 2021)
This study aimed to develop an animated video of the tsunami occurrence process as an effort to reduce disaster risk. This research refered to the ADDIE learning model which consists of 5 stages, including needs analysis, product design, product development, limited product testing and evaluation of products that have been developed. After validation and revision, the developed product was tested on a limited basis. The research subjects in this study were 10 students of SMP N 10 Palu and 5 Physics Teacher Candidates. Based on the results of data analysis showed that the average score of the feasibility test for the quality of animated videos was 3.75 in the